PROFESSIONAL VALUES AND GROUP SOCIALIZATION - Lucian MOCREI-REBREAN (Association of Social and Educational Innovation, 2023)
Any attempt to approach professional socialization involves taking into consideration the role of socio-economic structures, but also the implicit cultural aspects such as beliefs, community value systems and attitude towards work, or the ongoing traditions of the primary groups. The relationship, with maximum explanatory capacity, established between socializing institutions and socialized individuals, can be conceived, interpreted, and eventually described in alternative terms.  From a functionalist point of view, it can be said that professional socialization consists in a more or less effective internalization of an occupational culture. As part of this culture, professional values ​​contribute, together with traditions and norms, to the effective perpetuation of socially expectations and practices related to the professional role. Functionalism envisions culture as a socially external reality that exerts a constant pressure on the group life of a relatively passive social actor that is culturally receptive, and who acts predominantly voluntarily. On the other hand, from an interactionist perspective, socialized individuals are influenced, and in turn actively influence the social context by making it their own. As a result, professional roles are permanently constructed and reconstructed. I will show that, although it does not take into account the possibility of value conflict at individual level, a problem that can seriously affect the actual success of professional socialization, the functionalist paradigm satisfactorily explains the socio-cultural variation of value orientations at occupational group level.